Hybrid Materials Based on Carbon Nanotubes and Tetra- and Octa-Halogen-Substituted Zinc Phthalocyanines: Sensor Response Toward Ammonia from the Quantum-Chemical Point of View - Pavel Krasnov; Victoria Ivanova; Darya Klyamer; Dmitry Bonegardt; Aleksandr Fedorov; Tamara Basova (Sensors)
This paper presents the results of quantum-chemical modeling performed by the Density Functional-Based Tight Binding (DFTB) method to investigate the change in the band structure of hybrid materials based on carbon nanotubes and unsubstituted, tetra-, or octa-halogen-substituted zinc phthalocyanines upon the adsorption of ammonia molecules. The study showed that the electrical conductivity of these materials and its changes in the case of interaction with ammonia molecules depend on the position of the impurity band formed by the orbitals of macrocycle atoms relative to the forbidden energy gap of the hybrids. The sensor response of the hybrids containing halogenated phthalocyanines was lower by one or two orders of magnitude, depending on the number of substituents, compared to the hybrid with unsubstituted zinc phthalocyanine. This result was obtained by calculations performed using the nonequilibrium Green’s functions (NEGF) method, which demonstrated a change in the electrical conductivity of the hybrids upon the adsorption of ammonia molecules. The analysis showed that in order to improve the sensor characteristics of CNT-based hybrid materials, preference should be given to those phthalocyanines in which substituents contribute to an increase in HOMO energy relative to the unsubstituted macrocycles.